Спосіб мінімізації типових ускладнень при спінальній анестезії - Григор'єв, Сергій Володимирович; Перцов, Володимир Іванович; Григорьев, С. В.; Перцов, В. И.; Grigoryev, S. V.; Pertsov, V. I. (Харківська медична академія післядипломної освіти, 2019)
Резюме. Метою роботи було вивчення здатності низькодозової спінальної монолатеральної анестезії з використанням гіпербаричних розчинів бупівакаїну впливати на кардіогемодинаміку, респіраторну депресію, м’язове тремтіння, постпункційний головний біль, транзиторний ішемічний синдром і потребу в додатковій внутрішньовенній седації. Низькодозова спінальна анестезія виявила більший протективний ефект щодо кардіогемодинаміки: стабільний стан гемодинаміки на етапах оперативного лікування при виконанні низькодозової спінальної монолатеральної анестезії спостерігали в середньому в 3 рази частіше, ніж при стандартній спинномозковій анестезії. Використання монолатеральної техніки запобігало небезпечним змінам респіраторної функції на основному етапі в 2 рази більше, а після закінчення — в 4 рази. Озноб і тремтіння після монолатеральної спинномозкової анестезії спостерігали на основному етапі в 1,5 раза рідше, а після закінчення оперативного лікування — у 2,4 раза рідше, ніж при ортодоксальній спинномозковій анестезії. Резюме. Целью работы было исследовать влияние низкодозовой спинальной монолатеральной анестезии с использованием гипербарических растворов бупивакаина на кардиогемодинамику, респираторную депрессию, мышечную дрожь, постпункционную головную боль, транзиторный ишемический синдром и потребность в дополнительной внутривенной седации. Низкодозовая спинальная анестезия выявила больший протективный эффект в отношении кардиогемодинамики: стабильное состояние гемодинамики на этапах оперативного лечения при выполнении низкодозовой спинальной монолатеральной анестезии наблюдали в среднем в 3 раза чаще, чем при стандартной спинномозговой анестезии. Использование монолатеральной техники предотвращало опасные изменения респираторной функции на основном этапе в среднем в 2 раза больше, а по окончании операции — в 4 раза. Озноб и дрожь после монолатеральной спинномозговой анестезии наблюдали на основном этапе в 1,5 раза реже, а по окончании оперативного лечения — в 2,4 раза реже, чем при ортодоксальной спинномозговой анестезии. Abstract. Background. Spinal anesthesia methods are relevant and tend to spread in modern anesthetic practice. At that time, sympatholytic and toxic effects of local anesthetics, such as arterial hypotension, bradycardia, tremor and other neurological disorders, can lead to patient’s discomfort and somatic dangerous effects. The transient neurologic syndrome, which manifests itself as a local nerve root syndrome, is quite common, when using hyperbaric concentrations of local anesthetics. Post-puncture headache is a common consequence of spinal anesthesia, the pathogenesis of which, in addition to cerebrospinal fluid leak, also includes the toxicity of anesthetics. The purpose was to study of the influence of low-dose unilateral spinal anesthesia (USA) with hyperbaric bupivacaine solutions on cardiohemodynamics, respiratory function, muscle tremor, postpuncture headache, transient neurological syndrome and the need for additional sedation. Materials and methods. The study involved 68 patients, 41 women and 27 men, with the average age of 44.92 ± 6.38 years. Thirty-eight patients underwent a unilateral spinal anesthesia with 6.25–11.65 (7.50 ± 1.25) mg of 0.5% hyperbaric bupivacaine. Thirty patients were assigned to receive a standard USA, 15.0 ± 1.3 mg of isobaric bupivacaine solution was injected. On 5 perioperative stages, the number of cardiac contractions, blood pressure, the number of respiratory movements, SaO2, and the presence of shivering (yes/no) were determined. Dangerous changes on the haemodynamics were considered to be bradycardia below 55 beats per minute, or re-administration of cholinolytics, hypotension (mean blood pressure ≤ 60 mmHg), and re-administration of mesatone despite preoperative infusion preparation. Depression of respiration was considered to be present if SaO2 was ≤ 94 %, and the number of respiratory movements was ≤ 8 or above 22 per 1 minute. 24, 48 and 72 hours after the end of the operation, the presence of post-puncture headache and transient neurological syndrome (paresthesia) was evaluated by means of Numerical Rating Scale of pain — from 0 to 10 points. The Bromage scale was used to assess the effectiveness of sensorimotor block. Results. The Numeric Rating Scale did not demonstrate a significant difference on the early stages of the study. The statistically significant difference can be seen 3 hours after the surgery and on day 2 postoperatively in favour of the low-dose USA. After a day, the difference was not reliable, and in 3 days, the difference was also within the limits of statistical error. The quality of anesthesia on the Bromage scale had no significant differences in the comparison groups. Patients’ requests for additional intravenous sedation also did not have significant differences. Intraoperatively, 8 cases of minor sympatholytic muscle tremor were observed in the study group. In patients after standard USA, shivering of varying degrees, from single fasciculations to sweeping tremor, was observed in 11 cases (36.66 %, i.e., 1.5 times more often). After surgery, chills and shivering in the study group (3 cases) were observed almost 2.5 times less frequently than with the standard method (6 cases). After the introduction of a low dose of hyperbaric bupivacaine for unilateral anesthesia, cases of hypotension, bradycardia on the main stage of surgical intervention were found to be significantly less likely. With low-dosage technique, they were detected in every 9 patient (11.53 %), whereas in the standard method — in every 3–4 persons (31.25 %). After surgical treatment against nonselective spinal anesthesia, hemodynamic deviations were observed in 12.5 % of cases, with low-dose unilateral one — only in 4 %. Stable hemodynamics on the stages of surgical treatment, when using low-dose USA, was observed on average 3 times more often than with the standard USA. Cases of transient neurological syndrome were not observed in both groups. Low dose of local anesthetic 2 times decreases the number of dangerous changes in respiratory function, and by the end of the surgical intervention — 4 times. Conclusions. Low-dose spinal anesthesia showed a greater protective effect on cardiohemodynamics: a stable hemodynamics on the stages of surgical treatment with unilateral approach was observed on average 3 times more often than with a standard USA. The use of unilateral technique prevented the dangerous changes of respiratory function in the main stage 2 times, and by the end of the surgery — 4 times more often. Chills and shivering in USA on the main stage were observed 1.5 times less often, and after the end of operative treatment —2.4 times less often than with a standard USA.
Способ минимизации типичных осложнений при спинальной анестезии
Method for minimizing typical complications in spinal anesthesia
Keywords: спинномозкова анестезія; однобічна спінальна анестезія; періопераційні озноб і тремтіння; ускладнення спінальної анестезії; транзиторний неврологічний синдром; спинальная анестезия; односторонняя спинальная анестезия; периоперационные озноб и дрожь; осложнения спинальной анестезии; транзиторный невро- логический синдром; spinal anesthesia; unilateral spinal anesthesia; perioperative chills and shivering; complications of spinal anesthesia; transient neurological syndrome